British Association of Urological Surgeons suprapubic catheter practice guidelines – revised. (28th July 2020) - Jane Hall, Susan; Harrison, Simon; Harding, Chris; Reid, Sheilagh; Parkinson, Richard
Abstract : Aims: To report the updated and revised British Association of Urological Surgeons (BAUS) guideline on indications, safe insertion and subsequent care of suprapubic catheters (SPCs). Methods: The existing BAUS guideline on the insertion of SPCs was reviewed and has been updated in light of both activity and outcome data published since the original guideline was written. A systematic review of all new data from 2010 onwards was carried out. This updated guideline is largely evidence‐based but, where evidence was lacking, is based on the consensus of expert opinion from members of the BAUS Section of Female, Neurological and Urodynamic Urology. Results: Suprapubic catheterization is widely used and generally considered a safe procedure. There is, however, a small risk of serious complications including bowel injury. The BAUS has produced an updated consensus statement on SPC use with the aim of minimizing risks and establishing best practice. Areas for future research and development are also highlighted. This review has been commissioned and approved by the BAUS and the Section of Female, Neurological and Urodynamic Urology. Conclusions: While SPC insertion is generally regarded as a safe procedure, the risk of serious morbidity and death must always be considered and outlined to patients. These revised guidelines should assist in minimizing the morbidity associated with SPC usage.